Hubungan antara mental toughness dengan risk taking behavior pada pendaki gunung - Ivania Ardiningrum; Miftakhul Jannah (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2022)
Mental toughness memiliki peranan penting bagi pendaki gunung. Fungsi mental toughness yaitu untuk pertahanan diri pendaki ketika berhadapan dengan risiko selama melakukan pendakian. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara mental toughness dengan risk taking behavior pada pendaki gunung. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif korelasional. Penelitian ini menggunakan teknik purposive sampling dimana peneliti melibatkan 100 orang yang tergabung dalam organisasi Wanadri dengan rentang usia 18-50 tahun. Data penelitian diperoleh dari adaptasi skala mental toughness milik Clough et al, serta skala risk taking behavior milik Woodman et al. Teknik analisis data menggunakan uji korelasi product moment dengan bantuan Software JASP 0.15 for Windows. Hasil penelitian menunjukkan terdapat hubungan antara variabel mental toughness dengan risk takimg behavior dengan nilai koefisien sebesar 0.663 dan taraf signifikan 0.001 (p0.05). Hal ini menunjukkan bahwa terdapat korelasi positif diantara kedua variabel, sehingga mental toughness pendaki gunung dapat menentukan tingkat risk taking behavior yang dimilikinyaThe relationship between mental toughness and risk taking behavior in mountain climbersAbstractMental toughness has an important role for mountain climbers. The mental toughness function is for the climber's self-defense when dealing with risks during the ascent. This study aims to determine the relationship between mental toughness and risk taking behavior in mountain climbers. The method used in this research is correlational quantitative method. This study uses a purposive sampling technique in which the researchers involved 100 people who are members of the Wanadri organization with an age range of 18-50 years. The research data were obtained from adaptation of Clough et al's mental toughness scale, and Woodman et al's risk taking behavior scale. The data analysis technique uses the product moment correlation test with the help of JASP 0.15 software for Windows. The results showed that there was a relationship between the mental toughness variable and risk takimg behavior with a coefficient value of 0.663 and a significant level of 0.001 (p 0.05). This shows that there is a positive correlation between the two variables, so that the mental toughness of mountain climbers can determine the level of risk taking behavior they have.